2012
DOI: 10.1037/a0026914
|View full text |Cite
|
Sign up to set email alerts
|

Job burnout and depression: Unraveling their temporal relationship and considering the role of physical activity.

Abstract: Job burnout and depression have been generally found to be correlated with one another. However, evidence regarding the job burnout-depression association is limited in that most studies are cross-sectional in nature. Moreover, little is known about factors that may influence the job burnout-depression association, other than individual or organizational factors (e.g., gender, supervisor support). The current study seeks to address these gaps by (a) unraveling the temporal relationship between job burnout and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
238
0
12

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(265 citation statements)
references
References 106 publications
15
238
0
12
Order By: Relevance
“…Like many previous studies using this methodology in personality psychology (e.g., Jackson et al, 2012) and organizational psychology (e.g., Toker & Biron, 2012), our time intervals were uneven. However, this concern may be alleviated as reunification effects may decay over time (Fay & Sonnentag, 2002).…”
Section: Study Strengths Limitations and Future Researchmentioning
confidence: 67%
See 1 more Smart Citation
“…Like many previous studies using this methodology in personality psychology (e.g., Jackson et al, 2012) and organizational psychology (e.g., Toker & Biron, 2012), our time intervals were uneven. However, this concern may be alleviated as reunification effects may decay over time (Fay & Sonnentag, 2002).…”
Section: Study Strengths Limitations and Future Researchmentioning
confidence: 67%
“…This approach is appropriate to test lagged and reciprocal effects associated with individual differences in change. It has been used to study personality change (Jackson, Hill, Payne, Roberts, & Stine-Morrow, 2012) and dynamic relationships in I/O psychology (Toker & Biron, 2012). Figure 1 presents a path diagram of a bivariate LCS model with two factors: proactive personality and a work attribute.…”
Section: Analytical Strategymentioning
confidence: 99%
“…También dentro del ámbito educativo, el mindfulness se considera una herramienta eficaz de autorregulación emocional y prevención del estrés propiciando una mejor calidad de vida en los profesionales de la educación (Delgado et al, 2010). A pesar de estas evidencias, todavía hay una escasez de estudios sobre el potencial de la actividad física para proteger la salud negativa contra las consecuencias del estrés laboral (Gerber, Ingibjorg, Lindwall, & Ahlborg, 2014) y el desgaste profesional (Toker & Biron, 2012). El mé-todo Pilates, como se ha podido comprobar, tampoco es una excepción y precisa de nuevas investigaciones.…”
Section: Discussionunclassified
“…Furthermore, a reduced sense of superiority and a perceived loss of status are more characteristic for depressed than for those who are burnt-out (Brenninkmeyer et al 2001). The relationship between burnout and depression has been studied in numerous of studies and an association between the two of them has been observed (Ahola et al 2014;Fong et al 2016;Toker and Biron 2012). Additionally, in some studies, the distinctiveness between these two terms is not always attainable.…”
Section: Burnout and Depressionmentioning
confidence: 99%